ANALISA BREAK EVEN POINT (BEP) PADA RICE MILLING MACHINE “ BAROKAH “ DI TIRTO KABUPATEN PEKALONGAN - Edi Purnomo, Djauhar; Pujiono, Akhmad (Neraca, 2023)
Indonesia is an agricultural country where the majority of the population consists of farmers so that the agricultural sector plays an important role. The agricultural sector is a source of life for the majority of the population, especially for those who have their main livelihood as farmers. In addition, the agricultural sector is one of the important things that must be considered as a provider of food for the community. Profit planning requires a tool in the form of profit volume cost analysis. Costs, volume and profits are the three main elements in preparing a profit and loss statement for a business. In carrying out its operational activities, a management company will try to obtain and allocate resources in a way that is the cheapest in terms of cost and provides the most benefits in achieving business goals. This study discusses the analysis of the break even point (Break Even Point) in the Rice Milling Machine "Barokah" business sector to avoid losses. This type of research is quantitative research, the scope of the research being carried out focuses on income management from the Rice Milling Machine business. The population is all financial reports on the "Barokah" Rice Milling Machine in 2021 as well as samples used using samples through documentation. Furthermore, this research data was analyzed using the Break Even Point (BEP) mathematical model which is useful for providing solutions for a minimum amount of sales, this aims to anticipate losses in the Rice Milling Machine business.